Nutritional disorders and nutrition-related conditions: an underestimated clinical problem in systemic sclerosis - Anna Wojteczek; Michał Chmielewski; Zbigniew Zdrojewski (Rheumatology)
Nutritional disorders are significant but often underestimated complications in patients with systemic sclerosis (SSc). The most prevalent nutritional disorders in SSc are malnutrition, affecting up to 62.5% of patients, and sarcopenia, with a frequency of up to 42%. Thus, clinical vigilance is recommended for the detection of eating disorders in SSc patients, particularly those with gastrointestinal involvement, cardiopulmonary complications, an advanced disease stage, and high disease activity. Nutritional treatment should be carefully tailored to the patients’ clinical condition to ensure that it effectively addresses their specific needs. Studies focusing on enteral nutrition in SSc patients demonstrate its effectiveness in stabilizing or improving nutritional status in malnourished patients. In severe cases, parenteral nutrition offers viable options to support patient health. The findings highlight the importance of early nutritional assessment and intervention in improving patient outcomes and suggest that individualized nutritional therapy can be a critical component of comprehensive care for SSc patients.